1998
DOI: 10.2307/2534671
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control and Saving for Retirement

Abstract: In Lake Wobegone we believe in salting money away, not only as an investment but also to remove it as a temptation. Garrison Keillor' Some experts have called for easing penalties on early withdrawals from savings plans, believing people will invest more if they know they can get their money if they need it. But most Americans appear wary of such changes, fearful of the temptation to raid their own nest eggs. Sixty percent of Americans say it is better to keep, rather than loosen, legal restrictions on retirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
372
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(403 citation statements)
references
References 58 publications
9
372
1
4
Order By: Relevance
“…See, e.g., Laibson, Repetto, and Tobacman (1998). From this perspective, it might seem that taxes in the future, including estate taxes (and gift taxes, which may be incurred long after income is earned and has been saved) would have less of an effect on behavior.…”
Section: The Possibility That Transfers Are Not the Results Of Maximizmentioning
confidence: 99%
“…See, e.g., Laibson, Repetto, and Tobacman (1998). From this perspective, it might seem that taxes in the future, including estate taxes (and gift taxes, which may be incurred long after income is earned and has been saved) would have less of an effect on behavior.…”
Section: The Possibility That Transfers Are Not the Results Of Maximizmentioning
confidence: 99%
“…Several papers (surveyed in Poterba et al, 1996) found that these plans tend to increase savings among plan 9 See Laibson et al (1998). 10 See Madrian and Shea (2001), Choi et al (2001Choi et al ( , 2004a.…”
Section: Related Literaturementioning
confidence: 99%
“…In particular, although hyperbolic discounting may place greater weight on the interests of future generations, there are problems with incorporating hyperbolic discounting of utility into social cost-benefit analysis (Pearce et al, 2003;Groom et al, 2005). Because hyperbolic discounting can explain a range of perplexing human behaviours, including drug addiction (Gruber & Koszegi, 2001), sub-optimally low savings rates (Laibson, 1997;Laibson et al, 1998;Harris & Laibson, 2001), procrastination (ODonoghue & Rabin, 1999a,b;Benabou & Tirole, 2004) and various others (Akerlof, 1991), this paper does not make the normative recommendation that hyperbolic preferences be incorporated into optimal policy making. 4 On the other hand, it is important to understand the descriptive implications of what might happen if a planner does use hyperbolic discounting in making policy, if only so that we can be aware of potential problems before they arise.…”
Section: Literature Reviewmentioning
confidence: 99%